2022
DOI: 10.1111/os.13308
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Bridge Locking Fixator versus Traditional Locking Plates in Treating AO/OTA 32‐A3.2 Fracture: Finite Element Analysis and Biomechanical Evaluation

Abstract: Objective To compare the biomechanical behaviors of the spatial bridge locking fixator (SBLF), single locking plate (SP), and double locking plate (DP) for AO/OTA 32‐A3.2 fractures using finite element analysis and biomechanical tests. Methods Axial loading of 700 N was conducted on the AO/OTA 32‐A3.2 model via finite element analysis. The von Mises stress and the interfragmentary movement (IFM) were comparatively analyzed in the three configurations above. On the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Nevertheless, considerable controversy has arisen regarding the appropriate number of osteosynthesis plates required to ensure stability and avoid implant fracture [22]. Hence, the primary aim of this study was to investigate the biomechanical behavior differences produced using two osteosynthesis plates instead of only one for treating femoral shaft osteotomies [24]. Previous studies [22,25,26] have shown that double orthogonal locked plate constructions present higher stiffness than any other configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, considerable controversy has arisen regarding the appropriate number of osteosynthesis plates required to ensure stability and avoid implant fracture [22]. Hence, the primary aim of this study was to investigate the biomechanical behavior differences produced using two osteosynthesis plates instead of only one for treating femoral shaft osteotomies [24]. Previous studies [22,25,26] have shown that double orthogonal locked plate constructions present higher stiffness than any other configuration.…”
Section: Discussionmentioning
confidence: 99%
“…The locking plate and locking compression plate combine mechanical stability of a type‐1 external fixator with the benefits of internal fixation such as lower infection risk and lack of external interference [30]. Mechanical testing of LCP stabilized gap defects in vitro have documented superior strength against bending and compressive forces in vitro when compared to conventional dynamic compression plates, but questions have been raised regarding the fixation’s torsional strength [1–3, 14, 15, 21]. In a biomechanical study of tibiofemoral contact forces in sheep, Taylor et al documented significant axial force conveyed to the tibia from the tibiofemoral joint, but unlike humans, sheep experience a greater magnitude of craniocaudal and mediolateral sheer force originating at the stifle [31].…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of early loading and carefully monitored rehabilitation following plate fixation are common practices in human orthopedics to maximize fixation stability and reduce the risk of early fatigue, and immediate postoperative weightbearing in preclinical animal models poses a significant challenge to fixation longevity. Bridge plating osteosynthesis relies on a small degree of interfragmentary motion to stimulate callus formation, thus discouraging excessively stiff fixation [ 14 , 34 ]. Conventional dynamic compression plating requires adequate plate to bone contact during screw tightening to achieve desired stability between the plate and bone surface, and potential complications such as periosteal vascular compromise, stress risers, and loss of compression in compromised bone may lead to fracture complications [ 8 , 22 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen fourth-generation osteoporosic composite artificial left femurs (#3503; Pacific Research Laboratories, Vashon, DC, USA) were purchased in advance. 21 Referring to the coronal plane angles for embedment selected in the FEA, these artificial femurs were assigned into five groups randomly with three in each group. To ensure the consistency of the osteotomy distance and the embedding angle within each group, the purchased digital model of the fourth-generation osteoporotic composite artificial femur (#3503; Pacific Research Laboratory; Vashon, DC, USA) was conducted into Unigraphics NX (Siemens, Plano, TX, USA) to design the tooling for osteotomy and embedding.…”
Section: Osteotomy and Embedding Of Specimenmentioning
confidence: 99%